2015
DOI: 10.1111/bjso.12115
|View full text |Cite
|
Sign up to set email alerts
|

Identity appropriateness and the structure of the theory of planned behaviour

Abstract: In contrast to the cost-benefit, utility-based approach to decision-making implicit in models such as the theory of planned behaviour (TPB), the logic of appropriateness (March, 1994. A Primer on Decision Making: How decisions happen. New York, NY: The Free Press) describes decision-making in terms of heuristic decision rules that involve matching identities to situations. This research is the first to apply the logic of appropriateness in conjunction with the theoretical structure of the TPB and assessed whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Further, the effect of self‐identity remained when controlling for past behaviour. These findings provide an important extension to the body of research supporting the utility of self‐identity within the TPB (e.g., Rise et al., ), and also contribute to other areas of research supporting the importance of identity in guiding behaviour (e.g., Case et al., ; Fritsche, Barth, Jugert, Masson, & Reese, in press; March, ). Together, this research indicates that interventions aiming to influence behaviour may benefit from attempting to promote self‐identities consistent with performing the behaviour.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Further, the effect of self‐identity remained when controlling for past behaviour. These findings provide an important extension to the body of research supporting the utility of self‐identity within the TPB (e.g., Rise et al., ), and also contribute to other areas of research supporting the importance of identity in guiding behaviour (e.g., Case et al., ; Fritsche, Barth, Jugert, Masson, & Reese, in press; March, ). Together, this research indicates that interventions aiming to influence behaviour may benefit from attempting to promote self‐identities consistent with performing the behaviour.…”
Section: Discussionsupporting
confidence: 60%
“…That is, people consider their self-identity within a social context and use it as a heuristic tool to guide their behaviour (cf. Case, Sparks, & Pavey, 2016).…”
Section: Self-identitymentioning
confidence: 99%
“…Finally, the high conformity group strongly agreed with both questions (scoring a 10) and included 21.98 percent of the sample . While intentions to conform may not be the same as actual conforming behavior, research shows that identities do affect behavioral intentions, which then predict subsequent behavior (Ajzen ; Case, Sparks, and Pavey ).…”
Section: Methodsmentioning
confidence: 99%
“…We created a series of dummy variables including property crime with a victim, shoplifting, and violent offenses, with drink driving as the reference category. Given that our measure of the criminal identity standard may depend on the RAs that are received and that identities can affect attitudes (Case, Sparks, and Pavey ), we also control for how respondents viewed their offense before court or conference (Asencio ). Respondents indicated how wrong they felt their offense was before the court/conference ranging from totally right (1) to totally wrong (5) with the neither category coded as 3.…”
Section: Methodsmentioning
confidence: 99%
“…Stryker proposes that individuals behave in a manner consistent with their identity, progressively more so as this identity becomes more salient. Self-identity has previously predicted dieting intentions [ 35 ], low-fat diet consumption [ 24 ], low animal fat diet [ 36 ] and actual healthy eating behaviour [ 37 ]. A recent meta-analytic review of the inclusion of self-identity in TPB studies [ 30 ] supports its additive effects; regression analyses indicated that self-identity explained on average an incremental 6% of the variance in intention after controlling for the TPB constructs.…”
Section: Introductionmentioning
confidence: 99%